HOW GIMP SOFTWARE HELPS IN PREOPERATIVE DEFORMITY PLANNING - Yaacob, Norazira (International Journal of Allied Health Sciences, 2021)
The GIMP is a free software available online for image/picture manipulation programme. GIMP has been modified by Dr Selvadurai to use for deformity planning. It is a very useful programme for those who are not routinely doing the deformity corrective procedure as no fees required to be paid compares to that paid software. It can draw the mechanical or anatomical axis line and measure the joint orientation angle. Furthermore, it can cut the image and rotate it at the CORA or ACA. All the step of the planning can be saved and exported to the .png or .jpeg files and copied to power point for presentation. The presentation will show how to use GIMP with the case example.